Kinetic Spectrophotometric Methods for the Determination of Chloramphenicol in Pharmaceutical Preparations - Al-Ward, Hind S (Al-Nahrain Journal of Science, 2018)
Simple and sensitive kinetic methods are described for the determination of chloramphenicol in pure form and pharmaceutical preparations. The methods are based on oxidative – coupling reaction between reduced chloramphenicol (by zinc powder and concentrated hydrochloric acid) with promethazine hydrochloride in the presence of sodium periodate yielding a highly colored product at room temperature, the reaction is followed spectrophotometriclly at λmax= 590 nm. Initial rate and fixed time (at 20 minutes) methods are utilized for concentration determination. The calibration graphs were linear in the concentration ranges (2-20 µg.ml-1) and (0.5-30 µg.ml-1) respectively. The results were validated statistically and checked through recovery studies, and have been applied successfully for the determination of chloramphenicol in commercial dosage forms